Efficacy and safety of long‐acting intramuscular testosterone undecanoate in aging men: a randomised controlled study. (12th April 2013) - Tan, Wei Shen; Low, Wah Yun; Ng, Chirk Jenn; Tan, Wei Keith; Tong, Seng Fah; Ho, Christopher; Khoo, Ee Ming; Lee, George; Lee, Boon Cheok; Lee, Verna; Tan, Hui Meng
<x xml:space="preserve">Abstract</x> Objective To evaluate the efficacy and safety of long‐acting i.m. testosterone undecanoate (TU) in Malaysian men with testosterone deficiency (TD). Patients and Methods A total of 120 men, aged 40–70 years, with TD (serum total testosterone [TT] ≤ 12 nmol/L) were randomised to receive either i.m. TU (1000 mg) or placebo. In all, 58 and 56 men in the placebo and treatment arm, respectively, completed the study. Participants were seen six times in the 48‐week period and the following data were collected: physical examination results, haemoglobin, haematocrit, TT, lipid profile, fasting blood glucose, sex hormone‐binding globulin, liver function test, prostate‐ specific antigen (PSA) and adverse events. Results The mean (sd) age of the participants was 53.4 (7.6) years. A significant increase in serum TT (P < 0.001), PSA (P = 0.010), haematocrit (P < 0.001), haemoglobin (P < 0.001) and total bilirubin (P = 0.001) were seen in the treatment arm over the 48‐week period. Two men in the placebo arm and one man in the treatment arm developed myocardial infarction. Common adverse events observed in the treatment arm included itching/swelling/pain at the site of injection, flushing and acne. Overall, TU injections were well tolerated. Conclusions TU significantly increases serum testosterone in men with TD. PSA, haemoglobin and haematocrit were significantly elevated but were within clinically safe limits. There was no significant adverse reaction that led to the cessation of treatment.